Risk Factors Of Hypertension In The Elderly Within The Family : A Literature Review - Mustapa, Gesit Wira; Susanto, Tantut; Asmaningrum, Nurfika (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Hypertension is a chronic disease that often occurs in the elderly and contributes significantly to increased morbidity and mortality due to cardiovascular complications. This literature review aims to identify risk factors that influence the occurrence of hypertension in the elderly in the family environment through a literature review approach. Scientific articles published from 2019 to 2024 originated from PubMed, Garuda, and Google Scholar databases. Keywords used include “Hypertension,” “elderly.” “risk factor,” and “daily activites.” Ten article met the inclusion criteria and were analyzed further from the search results. The study results show that several main risk factors for hypertension in the elderly in the family include unhealthy eating patterns (excessive salt consumption), low physical activity, obesity, psychological stress, and low social support from family members. Genetic factors also play a role, but their interaction with lifestyle and family environmental conditions increases the potential for hypertension. Older adults who live in families with little attention to a healthy lifestyle or who experience social isolation tend to have higher blood pressure. Therefore, interventions involving families to increase awareness and play an active role in supporting older adults to adopt a healthy lifestyle, such as a low-salt diet, regular exercise, and stress management, are very important to reduce the prevalence of hypertension in this age group. Further Research is needed to develop effective family-based intervention strategies.